Dry matter accumulation and uptake of nitrogen, phosphorus and potassium by ryegrass (Lolium multiflorum Lam.) cultivar BARjumbo (Research, Society and Development, 2020)
Ryegrass (Lolium multiflorum Lam.) is one of the most used annual winter species for animal feed in southern Brazil. The objective of this study was to evaluate dry matter (DM) accumulation and uptake of nitrogen, phosphorus and potassium by ryegrass cultivar BARjumbo. The experiment was conducted under greenhouse conditions from the autumn until the spring of 2018. A completely randomized design with five replicates was used, with treatments consisting of 15 different evaluation periods (from 10 to 150 days after emergency - DAE). The plant height increased linearly, while for the tiller number, the highest value was 110 DAE. IAF was strongly increased between 30 and 100 DAE. DM yield was increased during all evaluation periods (between 10 and 150 DAE). The highest rates of DM yield increase occurred between 50 and 60 DAE. The N and P contents in shoot DM decreased according to plant age. For the K content, the values began to decrease only from 100 DAE. There were increases in N, P and K accumulations in shoot up to 120 DAE. From this date, the values decreased up to 150 DAE. The decreasing order of nutrient accumulation in the shoot was K > N > P, whereas in the root the order of accumulation was N > K > P.